EDITORIAL - Mohanty, B p (Journal of the Inland Fisheries Society of India, 2021)
JIFSI (The Journal of Inland Fisheries Society of India) is one of the oldest in its category and has the distinction of uninterrupted publication since 1969. Many stalwarts in inland fisheries research in the country, to name a few Padmashree (Dr.) V.G. Jhingran, Dr. Hiralal Chaudhuri (Father of Induced Breeding in India), Dr. V. R. P. Sinha Founder Vice Chancellor, Central Institute of Fisheries Education (CIFE) Deemed University, P. V. Dehadrai First DDG (Fisheries)-ICAR, Dr. S.D. Tripathi Director & VC, CIFE- Deemed University. World Food Price Laureate Dr. M. Vijaya Gupta, Shri B. N. Saigal, Dr. A. V. Natarajan, Dr. Y.S. Yadava, Director BOBP 1GO have been associated with publication of this journal.